Apropriação do patrimônio psíquico-social na formação de psicanalistas no Instituto DEEP: uma interface da Psicanálise com a teoria da atividade sóciohistórico-cultural - Granado, Selma Regina Pato Vila (2022)
This study aims to propose the concept of psychism-social funds as the dialogue between Psychoanalysis and the Socio-Historical-Cultural Activity Theory (TASHC), as well as to understand how the appropriation process of these funds takes place. In order to achieve these goals, this research specifically aims to: 1) define the concept of psychism-social funds through the articulation of the Psychoanalysis’ concepts with those of TASHC; 2) construe how the socio-historical-cultural and psychic process, revealed in the testimonies of three students from the DEEP Institute (Dialogues and Studies in Psychoanalysis), enabled the subjects to consciously own the experiences they have lived to become a psychism-social funds for these subjects; 3) understand which transformations (having the possession of these funds) appear in these three students’ discourses when dealing with their life experiences after this appropriation. Theoretically, this research is based on the Vygotskyan studies on language, activity, subject constitution, consciousness, crisis and perezhivanie, also on some key Psychoanalysis’ concepts: unconscious, ego formation, drive, incorporation, introjection, identification, repression, and transference. Methodologically, this study was designed using the Critical Collaborative Research (PCCol) approach. It had the participation of three students from the DEEP Institute who answered a questionnaire covering 14 questions regarding reflections, discoveries, desires, and learning throughout the Psychoanalysis course. Their answers were collected via WhatsApp audios which were transcribed and analyzed by the enunciative aspect of the argumentation (LIBERALI, 2013), which observes the thematic content revealed by the social values that surround the participants; and by the discursive aspect, which considers the thematic organization and the articulation amongst the ideas presented by the three students. The results reveal that the socio-historical-cultural and psychic process carried out in the course enabled participants' experiences to become a psychism-social funds through the transference phenomenon, the dramatic event and the perezhivanie. The course, as a place of crisis, was marked by the contradictions between the memories that the unconscious presents and the emotions caused by facing this content in a collective space. In this direction, the appropriation of the psychism-social funds takes place amid the drama of confronting the unconscious contents that always come up in practices of social interaction. Thus, through the transference process, the participants developed consciousness, making the egoic structure legitimate and progressively more powerful to take the psychism-social funds. Whether this was negative or positive, the experiences became a repertoire for dealing with life